EFFICACY OF HAIR REMOVAL WITH DIODE LASER SYSTEM (808NM) CORRELATE TO NUMBER OF TREATMENTS IN DARK SKIN LIBYAN PATIENTS - Rabab R. Elhassi; Salwa A ElDibany (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background and Objective:  The 808-nm wavelength Diode lasers is commonly used for hair removal. To date, the available spot sizes and repetition rates are defining factors in terms of penetration depth, treatment speed, and efficacy The 808nm wavelength diode laser can safely and successfully treat  dark pigmented skin. Study Design;  A total of 50 adult patients with skin types I–IV were  treated at 3-week intervals , the average of energy around from 10-50j\cm*2  were delivered  on a monthly bases treatment  into involved area by a single operator ,spot size  15*35mm standard. The device was set as short pulse (17ms), pulse rate (1 Hz-10Hz)  conducted at a private clinic at a private clinic  in ,Benghazi  city , Libya in the period from Sep 2019 to Dec 2022 . Results;Conclusions: Diode lasers can be used on dark pigmented skin with positive outcomes. Complications such as hypopigmentation, or hyperpigmentation occurred, but all were transient and resolved within a few months. Lasers Surg. Med. 28:150–155, 2001. © 2001 Wiley-Liss, Inc.